Group-Based Restorative Care Model For Improving Social Interaction Among Elderly In Nursing Home - Ni Made Riasmini (poltekkes kemenkes mataram, 2021)
An increasing proportion of the elderly population should be aware, because the main manifestation of the aging process experienced by the elderly can reduce ability to work, and the ability to perform the activity and social interaction with their environment. To overcome this problem, a group-based restorative care model is needed to increase the social interaction among elderly. This study aimed to obtain an overview of the effectiveness of the group-based restorative care model on the social interactions among elderly in nursing homes. The research design used a quasi-experimental with control group design with a sample size of 66 elderly who have been living in nursing home in the DKI Jakarta area. Data analysis used t-test and Mancova test. The results of the study found that there were differences in social interaction before and after the intervention in the intervention group, while in the control group there were no differences; there were differences in social interaction after the intervention between the intervention group and the control group; there was an effect of social support on social interaction. The recommendation is the group-based restorative care model can be used as a model for empowering the elderly in carrying out various activities in various health care settings in the community